Enhanced ultra high frequency EMI shielding with controlled ITO nano-branch width via different tin material types - Kim, Youngho; Kim, Noeul; Lee, Sang Hoon; Hyeong, Seok Ki; Lee, Jae Hyun; Lee, Jaeyeong; Bae, Jong Seong; Cho, In Sun; Choi, Jae Young; Kim, Soo Young; Yu, Hak Ki (Nanoscale, 2023)
The development of technologies for electromagnetic wave contamination has garnered attention. Among the various electromagnetic wave frequencies, for high frequencies such as those in the K and Ka ranges, there is a limitation of using only the properties of a single material. Therefore, it is necessary to improve the absorption coefficients by increasing the path of electromagnetic waves through internal scattering at an interface or a structure inside the material. Here, we accurately demonstrated the role of Sn in the growth of an indium tin oxide (ITO) nano-branch structure and grew high-density ITO nano-branches with the lowest thickness possible. Consequently, we obtained shielding efficiencies of 21.09 dB (K band) and 17.81 dB (Ka band) for a film with a thickness of 0.00364 mm. Owing to the significantly high specific shielding efficiency and low thickness and weight, it is expected to be applied in various fields.
Keywords: Absorption coefficients; Branch structure; EMI shielding; High frequency HF; K bands; Material's type; Property; Shielding efficiency; Ultra-high-frequency; Wave frequencies